Formulation of Brevibacillus agri and compost to improve growth and phytochemicals compound of Piper caninum herbal plant - Suriani, Ni Luh; Suprapta, Dewa Ngurah; Perveen, Kahkashan; Suarsana, I. Nyoman; Resiani, Ni Made Delly; Hamidah, Emmy; Rusdianasari; Alsulami, Jamilah A.; Parray, Javid A.; Ho, Ting Seng (Frontiers in Sustainable Food Systems, 2023)
Most herbal plant farming operations still rely on conventional methods, negatively impacting human health and the environment. However, by using rhizobacteria to boost the yield and quality of herbal plants, farmers can make a more environmentally responsible and safe choice for consumers. Therefore, the present study aimed to determine the dosage of Brevibacillus agri added to the medicinal plant Piper caninum to boost its growth and phytochemical content. Piper caninum is a popularly used medicinal plant with antifungal and antibacterial properties and the ability to improve the quality of mouse sperm. The investigation was carried out in a greenhouse using a randomized group approach. The results indicated that the most effective formula for promoting growth and enhancing phytochemical composition was F1 (100 g of compost and 3 kg of soil plus 1% Brevibacillus agri), which contained 1% B. agri. Treating the Piper caninum plant with 1%, 2%, or 3% B. agri yielded positive results, likely due to the bacteria's nitrogen-fixing ability and favorable outcomes for the IAA test and protease enzyme. Brevibacillus agri was also found to colonize the roots of Piper caninum and produce the phytochemicals butanoic acid, propanediol, and cyclopropane. In conclusion, using rhizobacteria in sustainable agriculture was highly effective, providing an ecologically responsible and safe alternative to conventional farming methods.